The Multiple V-Y Advancement Modification for the Surgical Correction of Cryptotia - Duc, Nguyen Quang; Tien, Nguyen Phuong (Archives of Plastic Surgery, 2023)
Cryptotia is a rare congenital auricular deformity among Caucasians but more common in Asians. Various operative techniques have been described, such as skin graft, V-Y plasty, Z plasty, and islands skin flap. Among those techniques, V-Y plasty has many advantages and is indicated for severe cases. However, several problems remain when this method is adopted, such as conspicuous scars and lowered hairline. To overcome these problems, the authors have developed a new technique, multiple V-Y advancement modification, which stitches the skin flaps together to a tight, discrete central focal point. This technique has the advantage of hiding scars behind the earlobe, providing enough skin for the deformed areas, minimizing the condition of the hairline being lowered and auriculocephalic sulcus depth.
Keywords: auricular; multiple V-Y; cryptotia; advancement flap